Education as a factor contributing to the development of nurses’ assertiveness - Sobczak, Marzena D.; Andruszkiewicz, Anna; Banaszkiewicz, Mariola (Polish Journal of Public Health, 2010)
Introduction. Nursing is a profession in which both education and a strong personality, integrity, assertiveness and empathy are the basis for proper functioning.Aim. The aim of the study was to determine the level of assertiveness in nurses, and to answer the questions whether their graduate and post-graduate education have an impact on assertive behaviours.Material and methods. The research covered working nurses of a hospital in Bydgoszcz, and three hospitals in Elbląg. A self-designed personal questionnaire was applied in the research in order to describe the socio-demographic features of the respondents and the self-designed Assertive Behavior Questionnaire based on the Assertiveness Map by M. Król-Fijewska.Results. The respondents with nursing bachelor’s degrees obtained the highest scores with respect to the global level of assertiveness. Also the respondents with master’s degrees obtained scores falling into the range of high values.Conclusions. Education is a factor contributing to the development of assertive behaviors.